Quality of Life, Anxiety and Depression in Children Caregivers with Brain Neoplasm - Nóbrega, Kenya Idamara Mendonça da (2011)
This work aims in socio-demographic terms children caregivers with brain tumors treated at a public hospital in Aracaju-SE and investigate this group perception as their quality of life, anxiety and depression. 32 caregivers  participated of a convenience pattern and three instruments were used: socio-demographic questionnaire, WHOQOL-bref and HADS. The sample showed that 100% of caregivers are mothers and grandmother. In evaluating of caregivers quality of life, the physical domain obtained 58.7 of rate; social 57.6, environmental 43.8; psychological, 55.6. The prevalence of anxiety was 50% and depression, 46.9%. The perception of  caregivers quality of life was moderate. The social do main was the essential factor to depression and physical domain was anxiety.